Properties of polystyrene concrete block with fly ash - Nurashyikin, Pauzi. (Universiti Malaysia Sarawak, UNIMAS, 2009)
This project reports the results of experimental investigation s into the properties of lightweight concrete blocks containing expanded polystyrene beads with fly ash . Lightweight concretes can be produced by replacing the normal aggregates in concrete depending upon the requirements of density and strength. This project use s expanded polystyrene beads as lightweight aggregate for replacement of coarse aggregate in the mixes . The main objective of this project is to determine the properties of EPS concretes containing fly ash. T otal of 126 samples of concrete blocks were prepared for this study. The properties studied were compressive strength, water absorption, weight and density, and heat resistance of the polystyrene concrete block with fly ash . The experimental results show that the compressive strength for samples with high percentage of poly styrene gives low compressive strength but samples with high percentage of fly ash give a higher compressive strength. The project also found that the optimum percentage of fly ash that can be replaced in the concrete is 30%. The properties of the block a re mainly influenced by the content of polystyrene beads in the mix and the percentage of fly ash .